Tailored nitrogen-containing polyaromatics - from surfaces to stacks - Delaney, Colm (Trinity College (Dublin, Ireland). School of Chemistry, 2016)
Chapter 1: This chapter gives a broad introduction to the subjects of graphene and nanographenes, which are discussed in subsequent chapters. Common methodologies for the synthesis of substituted polyphenylenes and hexabenzocoronenes are discussed. These prove an important preface to the concepts in the following chapters. An introduction to heteroatom substitution is also given, with particular emphasis placed on the influence of nitrogen atoms in the aromatic platform. Chapter 2: This chapter begins with an introduction to common modes of cyclodehydrogenation, used in both all-carbon and heteroatom-containing polyphenylenes, taking examples from a broad range of published research. The main body of the chapter then introduces a novel bond-forming phenomenon which is seen for nitrogen-containing polyphenylenes in the presence of Br2. C-C bond formation of this nature has never been documented before. This reaction is repeated, confirmed and tested through a range of varying conditions. The synthesis of a library of compounds allows for analysis of the limitations of this reaction and subsequent evaluation of potential mechanisms. The use of in situ NMR studies, combined with X-ray crystallography allowed for assignment of the reaction pathway and full characterisation of the final products, which possessed 2N, 4N and 6N substitution.
Embargo End Date: 2020-12-01
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin, 2016